Making Sense of Financial Capability Surveys around the World : A Review of Existing Financial Capability and Literacy Measurement Instruments - World Bank (Washington, DC, 2013)
This report will be particularly useful for policy makers and regulators who prioritize financial inclusion and/or financial literacy, or who are introducing financial education strategies according to the high-level principles developed by the organization for economic cooperation and development international network for financial education and recently endorsed by the G20 leaders. The review is intended to be a reference tool for policy makers, practitioners, and researchers interested in conducting a survey on these topics, and for those who need to identify the appropriate combination of methods for policy or research objectives. Chapter one examines how to identify, compare, and contrast existing measurement approaches in the area of financial literacy and capability, and in the related areas of financial inclusion and financial consumer protection. Chapter two discusses the role that surveys can have in informing policy and research in this area and provides examples of specific survey objectives. Chapter three describes and compares the content of the various instruments on financial capability, financial inclusion, and financial consumer protection, and provides examples of commonly used questions. Chapter four describes the methods used for survey implementation, and highlights technical issues that can affect data quality. Finally, chapter five describes the analytical methods that have been used to present the results and to construct indicators. Detailed information about each study is provided in standalone summaries in appendix B.